2012
DOI: 10.1039/c0ob00759e
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Evaluation of Lipase Performances Through Dynamic Asymmetric Cyanohydrin Resolution

Abstract: A dynamic resolution process based on multiple reversible cyanohydrin formation coupled to lipase-mediated transesterification is demonstrated. The resulting process resulted in the efficient evaluation of complex lipase performances in asymmetric cyanohydrin acylate synthesis. Dynamic systems were generated and resolved in situ, and the effects of the reaction conditions could be directly monitored for the overall system. By this concept, the enzyme activity, chemo- and stereoselectivity for all involved subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…The nitroaldol reaction is one of the first C-C bond-forming reactions used for complex dynamic systems, and its reversibility has been confirmed under basic conditions. 6,19 Hemithioacetal formation has also been utilized in both aqueous and organic solvents, 9,20,21 leading to the rapid formation of virtual dynamic systems in water, whereas base catalyzed real dynamic systems can be produced in organic solvents. Due to the discrete properties of each of the two reaction types, the equilibration features were first addressed.…”
mentioning
confidence: 99%
“…The nitroaldol reaction is one of the first C-C bond-forming reactions used for complex dynamic systems, and its reversibility has been confirmed under basic conditions. 6,19 Hemithioacetal formation has also been utilized in both aqueous and organic solvents, 9,20,21 leading to the rapid formation of virtual dynamic systems in water, whereas base catalyzed real dynamic systems can be produced in organic solvents. Due to the discrete properties of each of the two reaction types, the equilibration features were first addressed.…”
mentioning
confidence: 99%
“…This was also recently shown in a DCR study [ 4 ], where selective enzyme -mediated cyanohydrin transesterification could be used to resolve the dynamic systems and identify optimal constituents. This was also recently shown in a DCR study [ 4 ], where selective enzyme -mediated cyanohydrin transesterification could be used to resolve the dynamic systems and identify optimal constituents.…”
Section: Resolution Of Dynamic Combinatorial Cyanohydrin Libraries [ 4 ]mentioning
confidence: 57%
“…Individual Properties of Thiols(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) in Dynamic Transthiolesterification…”
mentioning
confidence: 99%
“…18,[21][22][23][24]27,28 It was shown that similar enantiomeric excesses (ees) could be obtained with both solvents; however, in toluene, higher conversions and reaction rates were observed. Among the enzymes tested, viz.…”
mentioning
confidence: 83%